The climatic suitability of New Zealand for Cirsium arvense and its biological control agent Cassida rubiginosa - Graeme W. Bourdôt; Shona L. Lamoureaux; Michael G. Cripps; Darren J. Kriticos; Alasdair Noble; Jessica M. Kriticos (Biological Control)
The leaf-feeding beetle, Cassida rubiginosa, was introduced into New Zealand from Europe in 2007 as a biological control agent for Cirsium arvense (Californian thistle) and is now widely distributed. To determine the extent to which geographically variable climate might explain its observed sporadic impact, we developed a climate-niche model for each of the species using CLIMEX. The models reveal that the climate throughout most of New Zealand is variably suitable for both species, although everywhere relatively less suitable for the beetle. However, we found no evidence that this climate suitability bias favouring the thistle explains the sporadic impact of the beetle. First, 64 geographically separate beetle populations classified by field observers according to their impact on the thistle (‘none’, n = 29; ‘low’, n = 22; ‘high’, n = 13) showed no relationship with the modelled climate suitability (Ecoclimatic Index) of their locations for either the beetle or the thistle. Second, the two models reveal a similar climate suitability bias favouring the thistle throughout much of the species’ ‘eco-climatic suitability space’ in their native range (Eurasia) where the beetle is a widespread natural enemy of the thistle. Hypothetical explanations for the sporadic impact of the beetle in New Zealand are explored, including lack of suitable overwintering habitat, predation, and incompatible thistle control operations. We conclude that in general, climate suitability, while a necessary condition, is alone insufficient for the success of a weed biological control program, and that non-climatic habitat factors may often explain spatially patchy impacts of natural enemies such as C. rubiginosa.